Optimization of Brain Function Learning (Neocortex) Through Neuroscience Based on Islamic Literature to Improve Behavior of Primary Students - Zulfitria Zulfitria; Zainal Arif; Tyasti Aryandini (AL-ISHLAH: Jurnal Pendidikan, 2022)
Deep networks in human brain can develop representations that are a better match to recordings in the neocortex of humans as existing models in neuroscience. This suggests that deep learning captures something important about how our own brains works. Islamic education curriculum neuroscience such as Islamic manners lesson,  apply learning methods  for  the  development  of  intellect  learners  so  in  the  formation  of  character  can  maximize  the  performance  of  sense and   neuroscience  of  learning students  are  given  the  opportunity  to     actively     construct     knowledge     through     learning, thus     neuroscience  learning  combined  with  a  variety  of  disciplines  so  integrated into the mainstream of the formation of character especially character of polite and disciplined through Islamic literacy lesson. This research uses mixed methods these following approaches; Literature study and also Class Action Research in three cycles. The results of these research Educational Neuroscience as one of the fields of study of neuroscience specializes in its studies in the field of education from a neuroscience perspective.In learning Islamic fairy tale literacy which was carried out on 3rd grade students of SDIT Aulady, with three students as the object of this research, 3 models of Islamic fairy tale literacy learning were carried out.